Maxine's tree - Léger, Diane Carmel, 1957- (Victoria, BC : Orca Book Publishers, 1990)
Maxine's idea to save her favorite tree and the others that grew in the rainforest in the Carmanah Valley on Vancouver Island inspires other visitors to follow her example.
3 21 31 43 53
Keywords: Trees -- Juvenile fiction; Rain forests -- Juvenile fiction; Nature conservation -- British Columbia -- Juvenile fiction; Children's stories. -- Juvenile fiction